Assessment of brain haemodynamic responses using optical topography modality - Hani, A.F.M. (Institute of Electrical and Electronics Engineers Inc., 2015)
Neuroimaging studies have shown that negative mood states will impair the working memory (WM) functions that affect haemodynamic conditions at the prefrontal cortex (PFC) region. Compared to other neuroimaging tools, haemodynamic responses in surrounding brain surfaces can be assessed feasibly and with less constrained using Optical Topography (OT). This paper presents near infrared spectroscopy (NIRS) signal analysis technique and OT brain haemodynamic assessment methods to investigate sensorimotor and working memory tasks, without biasing of mood. The continuous OT measurements for finger-tapping task and N-back tasks should result in significant task activation on the lateral motor cortex region and PFC region respectively. Findings from the first study confirmed the phenomena of contralateral motor cortex activation. In the second study, it is found that larger haemodynamic responses are associated with N-back WM task with higher difficulty. Â© 2015 IEEE.